PENGARUH KOMITMEN, SISTEM ADMINISTRASI, SUMBERDAYA, PENGHARGAAN, DAN SANKSI TERHADAP PENYUSUNAN APBD BERBASIS KINERJA DI SKPD PROVINSI BENGKULU - Yetti Afrida Indra (Jurnal Bisnis dan Ekonomi, 2017)
This research intent to know and analyse the factor that influence of Budgeting of Regional Revenue Expenditure (APBD) process based on erformance at Bengkulu Regency Government. With analyse that is done, therefore will get to know commitment of organization influence, administrasion system, human resources, reward, and punishment of Budgeting of Regional Revenue Expenditure (APBD)process based on performance at Bengkulu Regency. This research is executed at Bengkulu Regency Government by distributing questionnaires in each The Managerial Performance of the Work Unit (SKPD) to be filled by chief of The Managerial Performance of the Work Unit (SKPD) and planning division as respondents. Number of respondents is 104 of 52 The Managerial Performance of the Work Unit (SKPD) at Bengkulu Regency. The result of this research proves that commitment of organization influence, administrasion system, human resources, reward, and punishment have an effect on significant Budgeting of Regional Revenue Expenditure (APBD)process based on performance simultaneously. Partially, commitment of organization influence, administrasion system, human resources, reward, and punishment have an effect on significant Budgeting of Regional Revenue Expenditure (APBD)process based on performance, but the one has the biggest influence to Budgeting of Regional Revenue Expenditure (APBD)process based on performance is punishment. The result of this research also proves that adjust R2is 0,47, that is show that 47,4% of variety Budgeting of Regional Revenue Expenditure (APBD) process based on performance shown by variety of the six independent variable, commitment of organization influence, administrasion system, human resources, reward, punishment. Keywords: commitment , administrasion system, human resources, reward, punishment, budgeting ofregional revenue expenditure (apbd) based on performance